PENGARUH FREE CASH FLOW, PROFITABILITAS DAN DEBT TO EQUITY TERHADAP RASIO DEVIDEN - Fathonah, Nur; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The business practitioners in the company in the making of decision of dividend sharing to the shareholders often encounters a problem between the management of the company with the shareholders, so that it is required to notice some factors which have influenced in dividend sharing. This research is meant to find out how great some factors i.e. Free Cash Flow (FCF), Return on Investment (ROI) and Debt to Equity Ratio (DER) have an influence to the Dividend Payout Ratio (DPR). The samples are 15 manufacturing companies which are listed at Indonesia Stock Exchange (IDX) during the 2011-2013 periods. The research sample has been selected by using purposive sampling technique. The analysis instrument has been done by using multiple linear regressions. Based on the result of the research, it shows that the independent variables of FCF and ROI does not have any significant influence to the DPR, whereas DER has significant and negative influence to the DPR. The result of regression model feasibility test of FCF, ROI and DER variables have significant influence to the DPR which can be proven by the value of sig-F is smaller than significance of 5% and the value of Adjusted R Square is 17.2%.Keywords : Dividend Payout Ratio, Return On Investment, Debt to Equity, Profitability